Formulation of Peel-Off Gel Mask From Manilkara Zapota (L) P. Royen Leaves Extract and Antibacterial Activity Against - K Syifa Fauziyah; Senda Kartika Rakainsa (Journal of Science and Technology Research for Pharmacy, 2023)
Sawo leaves contain alkaloids, flavonoids, tannins, saponins and steroids which are antibacterial. This study aims to obtain the best concentration of Sawo leaf ethanol extract (Manilkara zapota (L) P. Royen) formulated as a peel-off gel mask preparation based on antibacterial activity test against Staphylococcus epidermidis bacteria. This study used laboratory experimental method. Sawo leaf extract peel-off gel mask preparation formula was made with concentration variations of 0.1%; 0.3%; 0.6%; 2.5%; 5% and 10%. Sawo leaf plant extract was obtained by maceration using 96% ethanol solvent. Identification of compounds was carried out using phytochemical screening, spray TLC and Bioautography TLC. Antibacterial testing of extracts was carried out using solid dilution and liquid dilution methods. The antibacterial test of the preparation using the wells diffusion method had the largest diameter of the inhibition zone at a concentration of 8% with an inhibition zone diameter of 14.1 mm and the inhibition ability was categorized as strong. It can be concluded that the concentration of 2%; 4%; 6%; 8% is good to be formulated as a peel-off gel mask preparation and is categorized as strong inhibition ability.